THE ROLE OF FOLK HANDICRAFTS IN NATIONAL CULTURE AND THE EDUCATION SYSTEM (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article examines the role of folk handicrafts in preserving national culture and integrating traditional values into the modern education system. Folk handicrafts are considered an important component of cultural heritage that reflects the historical experience, worldview, and aesthetic ideals of the people. The study highlights the educational potential of folk handicrafts in developing students’ social, cultural, and creative competencies. It also emphasizes their significance in fostering national identity, respect for cultural traditions, and practical skills through the educational process. The integration of folk handicrafts into formal education contributes to the formation of spiritually rich, socially active, and creatively oriented individuals.